AMORE treatment as salvage treatment in children and young adults with relapsed head-neck rhabdomyosarcoma. (February 2019) - Vaarwerk, Bas; Hol, Marinka L.F.; Schoot, Reineke A.; Breunis, Willemijn B.; de Win, Maartje M.L.; Westerveld, Henrike; Fajardo, Raquel Davila; Saeed, Peerooz; van den Brekel, Michiel W.; Pieters, Bradley R.; Strackee, Simon D.; Smeele, Ludi E.; et al.
Highlights: Treatment options after relapsed head and neck rhabdomyosarcoma (HNRMS) are limited. A salvage AMORE procedure is often one of the few remaining curative options. In this study we show the results of salvage AMORE treatment in our institution. If salvage AMORE is considered feasible, it could result in long-term survival. The 5-year overall survival was 54% in this cohort of 18 patients. Abstract: Background and purpose: Survival after relapse of head and neck rhabdomyosarcoma (HNRMS) after prior external beam radiotherapy (EBRT) is poor, since options for adequate local treatment are often lacking. In this study we describe our experience with salvage AMORE in patients with relapsed HNRMS after prior EBRT. Materials and methods: Patients with relapsed HNRMS after prior EBRT in which salvage AMORE treatment was considered feasible were analysed; this includes patients with parameningeal, head and neck non-parameningeal and orbital localization. AMORE treatment consisted of Ablative surgery, MOuld technique brachytherapy and surgical REconstruction. Results: In total 18 patients received salvage AMORE treatment; nine patients had relapsed parameningeal (PM) RMS, two patients had relapsed head and neck non-parameningeal RMS (HN-nonPM) and seven patients had relapsed orbital RMS. Local control rate was 67% and 5-year overall survival was 54% (95% confidence interval: 31–78%); 3/9 patients with PM RMS, 0/2 patients with HN-nonPM RMS and 6/7 patients with orbital RMS were alive after a median follow-up of 8.6 years. One patient with PM RMS survived more than 5 years after which he died from a secondary cancer. Six patients developed a local relapse (of which one patient also developed a distant metastasis) and two patients developed distant metastases. Conclusions: Salvage AMORE treatment is a feasible and effective local therapy approach even after prior EBRT. Since salvage AMORE treatment is sometimes the only curative option in patient with relapsed HNRMS, we encourage physicians to consider salvage AMORE treatment for patients with relapsed HNRMS after prior EBRT.